“Competency-Based Approaches in Enhancing Physical Education Teacher Training in Higher Education” - Musayev Otabek Qudratovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the use of competency-based approaches to enhance the training of physical education teachers in higher education. It focuses on integrating theoretical knowledge, practical skills, and reflective practices to improve professional competencies. The study emphasizes the role of interactive learning, digital tools, and competency-based methods in optimizing lesson quality, fostering student engagement, and promoting holistic development. Strategies for the effective implementation of these approaches in teacher education programs are also discussed.